To analyze the Temperature distribution of Helical Fin Profile of engine through CFDinvestigation - Saurabh Bachakaiyan (AG Volumes, 2021)
In order to convert the non-circular ducts into circular pipes, hydraulic diameter is used. This phrase, which refers to a circular tube, may be used to compute a variety of different things. The area of the cross-section and the perimeter of the wetted cross-section are represented by A and P in the equation below. 2D design is changed to 3D design for this study, and CFD results have been compared. Within the fins, water as well as ethylene glycol was also circulated, and also the effects were examined. As a result, the current study contributes to revealing and expanding the potential of helical fins with ethylene glycol in improving total heat exchanger performance while also lowering material costs for design engineers as well as manufactures